Phytochemical Evaluation of Ethanolic Extract of Cassytha Filiformis (Linn) Through GC-MS Analysis - P. Sudha Kesavarthini (Journal of Global Pharma Technology, 2019)
Medicinal plants have had a crucial role in human culture and civilization. The present study was carried for the preliminary phytochemical analysis of the ethanolic extract of the plant Cassytha filiformis (Linn) belongs to the family Lauraceae. Bioactive constituents in the ethanolic extract of Cassytha filiformis (Linn) was analysed by GC-MS analysis. In GC-MS analysis, around one hundred and fifty eight compounds were present, in which many compounds where not reported for their biological properties. The presence of various bioactive compounds confirms the application of Cassytha filiformis (Linn) for various diseases by traditional use.Keywords: Cassytha filiformis (Linn); Lauraceae; GC-MS analysis.